Modern weapons and military equipment for issue 01/2014 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Aged but Upgraded From Mall to Frontline Armored Economy Polish PL-01 combat vehicle concept rolled out Russia to establish 40 more army brigades by 2020 Japan to develop stealth-detecting long-range radar Turkey selects Chinese HQ-9 SAM for T-Loramids